Ekspresi Temporal Gen OsFTL9 Pada Padi (Oryza sativa L.) kultivar Cempo ireng dan Cempo abang - , PUPUT NURAINI F ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cempo ireng and Cempo abang are rice local varieties which are cultivated at Yogyakarta region. They have a high nutritional value because of anthocyanin and minerals content. Cempo ireng has a long harvest period which is 150-180 days after planting. The study of genes which are related to flowering time in two varietes of Indonesia local rices is needed. One of the flowering genes in rice is OsFTL9. The purpose of this research is to study the temporal gene expression of OsFTL9 in Cempo ireng and Cempo abang rice. The several stages of this research are RNA isolation from leaves blade taken periodically every 10 days , cDNA synthesis and amplification of Ubiquitin gene as internal control and OsFTL9 gene. The result showed that the heading date of Cempo ireng at 118 days after palanting (DAP) and for Cempo abang at 55 DAP. OsFTL9 in Cempo ireng is expressed at 80, 91, 100, 109, and 120 DAP, meanwhile OsFTL9 in Cempo abang is expressed at 40, 51, 60, and 70 DAS. The expression of OsFTL9 in Cempo abang is also expressed after heading date.